DARI KERATON KE PASAR: INDUSTRI PRIBUMI DI DAERAH YOGYAKARTA 1830 – 1930-AN - Anton Haryono (Humaniora, 2009)
This article deals with the development of theindigenous industry in Yogyakarta during the colonialperiod (1830s – 1930s). It is concerned with three aspects:the diversity, absorptive power, and achievement of theindigenous industry. The results showed that theindigenous industry of the colonial era in Yogyakarta had avast spectrum and was capable of developing dynamicallyalthough it never constituted the main stream of thesociety’s economic life. In 1930, its ability to absorbworkers was the highest in Java and Madura, and not muchdifference was found from that of the agriculture. Besides,some branches of the indigenous industry in Yogyakartafound wide markets for their products. The longestablished manufacturing tradition and the increase ofmoney circulation since 1830 were found to be factorsaffecting the dynamics of the Yogyakarta’s indigenousindustry.